ANÁLISE MORFOLÓGICA DO SISTEMA REPRODUTOR MASCULINO DE JOVENS E ADULTOS DE Loxosceles intermedia MELLO-LEITÃO (1934) (ARANEAE: SICARIIDAE), COM ÊNFASE NOS SEGMENTOS DO DUCTO E DA AMPOLA: UMA PERSPECTIVA EVOLUTIVA - Margraf, Aline (2009)
Loxosceles intermedia is a poisonous species widely distributed in the region of Curitiba and Campos Gerais of the Paraná State. There are descriptions in the literature concerning the reproductive behavior of this species and, more recently, studies have been carried out in order to describe the post-embryonic development of the female reproductive system. The adult male reproductive system is composed by two testicles connected to the vas deferens by two structures, a duct and an ampulla, not yet described for other spider species. Then in this work were described the morphological aspects of the development of the male reproductive system, the morphology of the duct and ampulla in the adult male and discussed possible functional and evolutionary implications of this segments on reproduction of L. intermedia. For the analysis in light microcopy, male animals at different stages of the development were etherized and sacrificed. Their abdomens were removed and fixed in 4% paraformaldehyde/ 0.1 M phosphate buffer, pH 7.4, and embedded in historesin (Leica). Subsequently, the serial 5 Tm sections were submitted to HE staining and PAS reaction. For the analysis in SEM, adult male animals were dissected and their whole testis-duct-ampulla was removed and fixed in 0.2 M sodium cacodilate, 2.5% glutaraldehyde and 2% paraformaldehyde, pH 7.4. The tissues were dehydrated and dried in alcohol series and critical point, respectively. Subsequently, the tissues were coated with gold and analyzed by SEM. Considering the fact that the organs of the male reproductive system of L. intermedia are tiny and fragile, which makes them difficult to dissect for observation in SEM by the usual methods, in this work was also evaluated some protocols, using paraffin, paraplast or PEG (for short and long time of infiltration) as infiltration medium, for obtaining serial sections, as well as three adherence substances to slides (5.5% albumin, 0.1% gelatin and 1% gelatin, the tissues samples were submitted of infiltration and 20 Tm sections were obtained, placed on glass slides, washed with solvent or water, dried at room temperature, coated with gold and analyzed in SEM. Infiltration with PEG for a short time and adhesion with 1% gelatin was found to be the best protocol resulting in the maintenance of the cell shape and tissue characteristics. Following the development of the male reproductive system of the brown spider it was observed that the maturation of the testis is the first event to take place. After the appearance of synspermium inside the testicles, the differentiation of the duct, ampulla and vas deferens is observed, and finally the external modification of the palps in copulatory organs occurs. In adult male, the tissue of the duct is composed of a non-secretory epithelium, without a defined lumen. The function of the duct is probably the selection of viable sperm cells. The ampulla wall is composed of a secretory epithelium whose glycoprotein secretion involves the synspermium. The secretion released by the ampulla could be involved in distinct aspects of the functionality of the gametes. The ampulla secretion could also be related to mechanisms of sexual selection, not yet established for this species of spider. In conclusion, this morphological novelty in L. intermedia male reproductive system appears to constitute an important evolutionary event on spider reproduction.